Clinical assessment of suspected damage from hand-held vibrating tools. - Ekenvall, L. (Scandinavian Journal of Work, Environment & Health, 1987)
The case history is still the cornerstone in the clinical assessment of suspected vibration injury. Objective tests to verify the symptoms are needed for legal reasons in insurance cases and for research purposes. The minimum requirement of a test used to obtain objective signs of Raynaud's phenomenon is that patients with vibration-induced white finger be evaluated along with symptom-free, but vibration-exposed, subjects for reference. The measurement of systolic blood pressure in the finger after local finger and general body cooling is a test that has been evaluated in this way, as has restitution of finger temperature after local cooling and ischemia combined with general body heating. If neurological symptoms are present, electroneurographic examination is essential since carpal tunnel syndrome, a treatable condition, is common in vibration-exposed patients. Measurements of vibration and temperature thresholds are complementary examinations. The so-called vibrogram may be a method with which to obtain objective neurological signs of vibration injury, but the test needs further evaluation. Until more is known of the pathophysiological mechanisms behind the disease, the patient's description of his symptoms, combined with a detailed exposure history, will remain essential for a diagnosis of vibration injury--irrespective of the results of the tests used.